2018
DOI: 10.1177/1753425918800555
|View full text |Cite
|
Sign up to set email alerts
|

Matrine induces apoptosis via targeting CCR7 and enhances the effect of anticancer drugs in non-small cell lung cancer in vitro

Abstract: This study mainly investigated the effects of matrine on cell apoptosis and the effects of anticancer drugs in non-small cell lung cancer (NSCLC) cell lines (A549 and LK2 cells). The results showed that matrine (≥10 μM) caused a significant inhibition on cell viability and 10 and 100 μM matrine induced cell apoptosis via influencing p53, bax, casp3, and bcl-2 expressions in A549 cells. In addition, matrine significantly down-regulated C-C chemokine receptor type 7 (CCR7) expression, and blocking the down-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…22 Not surprisingly, Matrine promoted apoptosis via affecting apoptosis-related protein expression, including Bcl-2 and Caspase3; importantly, Matrine could inhibit drug-resistance of NSCLC cells for chemotherapeutic drugs with a dosage-dependent manner, implying the anti-cancer potentials of Matrine in NSCLC. 23 Analogous tumor inhibition impacts by Matrine in NSCLC were also confirmed by other researchers. 24,25 As we all know, it was widely reported that circRNAs exhibited their effects through functioning as miRNA sponges through competing endogenous RNAs network.…”
Section: Discussionsupporting
confidence: 59%
“…22 Not surprisingly, Matrine promoted apoptosis via affecting apoptosis-related protein expression, including Bcl-2 and Caspase3; importantly, Matrine could inhibit drug-resistance of NSCLC cells for chemotherapeutic drugs with a dosage-dependent manner, implying the anti-cancer potentials of Matrine in NSCLC. 23 Analogous tumor inhibition impacts by Matrine in NSCLC were also confirmed by other researchers. 24,25 As we all know, it was widely reported that circRNAs exhibited their effects through functioning as miRNA sponges through competing endogenous RNAs network.…”
Section: Discussionsupporting
confidence: 59%
“…Drug combination therapy is therefore a common and efficient strategy for cancer treatment. Matrine, an active component of Sophora flavescens, has antitumor effects in breast, ovarian, non-small cell lung and colorectal cancers, similarly to that of cisplatin in liver cancer (17)(18)(19). A study by Li et al (20) reported that treatment with matrine in combination with docetaxel inhibits the proliferation and migration of tumor cells in androgen-resistant prostate cancer, indicating the potential antitumor effects of matrine in combination with chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, enhancement of efficacy and/or toxicity due to drugdrug interactions has been a key consideration in the development of new drugs in pre-clinical and clinical investigations (Pai et al, 2018). Pu et al showed that MT combined with cisplatin, 5fluorouracil, and paclitaxel, respectively, effectively inhibited the proliferation of A549 cells and showed dose-dependent anticancer effects (Pu et al, 2018). It has been reported that a combination of MT and cisplatin synergistically inhibited proliferation, and induced apoptosis of rhabdomyosarcoma (RMS) RD cells, through a mechanism involving inhibition of mRNA expression of XIAP mRNA .…”
Section: Drug-drug Interactions Of Mtmentioning
confidence: 99%
“…Pu et al. showed that MT combined with cisplatin, 5-fluorouracil, and paclitaxel, respectively, effectively inhibited the proliferation of A549 cells and showed dose-dependent anticancer effects ( Pu et al., 2018 ). It has been reported that a combination of MT and cisplatin synergistically inhibited proliferation, and induced apoptosis of rhabdomyosarcoma (RMS) RD cells, through a mechanism involving inhibition of mRNA expression of XIAP mRNA ( Li et al., 2016 ).…”
Section: Drug-drug Interactions Of Mtmentioning
confidence: 99%